Pendampingan Bahaya NAPZA di Kalangan Pelajar SMP Negeri 2 Bulu Temanggung - Siti Lailiyah; Salis Wahyu Hidayati; Pamungkas Stiya Mulyani; Maryono Maryono; Robingun Suyud El Syam (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
Drug abuse (NAPZA) has become a serious threat among students and poses significant risks to their physical health, psychological well-being, and future development. Therefore, preventive efforts through structured education and mentoring programs are essential. This community service activity aims to describe the process and outcomes of a drug abuse prevention mentoring program conducted at SMP Negeri 2 Bulu, Temanggung. The program applied a participatory approach consisting of four stages: coordination with the school, educational socialization on the dangers of drugs, follow-up activities through discussions and student reflections, and evaluation to measure students’ understanding. The educational sessions were delivered using interactive lectures, question-and-answer methods, and visual learning media to enhance students’ engagement and comprehension. The results indicate an increase in students’ knowledge and awareness regarding the types, impacts, and prevention strategies of drug abuse. Moreover, students demonstrated more positive attitudes and a stronger commitment to avoiding drugs as a form of self-protection for their health and future. This program is expected to serve as a school-based preventive education model to reduce drug abuse among students through collaboration between teachers, schools, and the wider community.